THE INFLUENCE OF MONEY SUPPLY, ECONOMIC GROWTH AND EXPORTS ON INFLATION IN INDONESIA - Hasty Lesiani; Wardatul Husna; Murtala; Mutia Rahmah; Rahmatunnisa (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
This study aims to determine the effect of the amount of money in circulation, economic growth, and export on inflation in Indonesia. The data used in this study is a time series from 1980-2020 obtained from the Central Bureau of Statistics and Bank Indonesia. The analytical model used in this study is the Autoregressive Distributed Lag model. The data is processed using the Eviews application. The results of the study show that in the short term, the money supply has a positive and significant effect on inflation, as well as in the long term. Economic Growth in the short and long term has a negative and significant effect on inflation, while exports have a negative and insignificant effect on inflation in the short and long term.